Effects of strategic leadership, organizational innovativeness, information technology capability on effective strategy implementation - Palladan, Ahmad Aliyu (2017)
This study investigated the determinants of perceived organizational strategy implementation among public tertiary institutions in Nigeria. Primarily, the study explored the effects of Strategic Leadership (SL), Organizational Innovativeness (OI) and Information Technology Capability (ITC) on Effective Strategy Implementation (ESI). More precisely the direct effect of SL, OI and ITC on ESI were assessed. The study also examines the moderating effect of ITC on SL and OI on ESI. Thirteen (13) public tertiary institutions were considered by the research. One hundred and four (104) deans who serves as the research respondents were sampled out of the population total of 143 deans from the institutions. Hand delivery of questionnaires was used to solicit information from the respondents. Partial Least Squares Method (PLS 2) algorithm and bootstrap techniques were used to test the study hypotheses. The results provided support for most of the hypothesized relationship for the study. Specifically, SL, OI and ITC are found to be significant and positively affect organizational ESI. Additionally, ITC has been found to significantly moderate the relationship between SI and perceive ESI. While negative moderating effect of ITC was found between OI and perceive ESI. PIIT theory as well as Diffusion of Innovation Theory were partly considered as probable reasons for the negative finding. Therefore, significant positive effects of SL, OI and ITC suggest that the variables are important in facilitating ESI. As such, public tertiary institutions should be encouraged to demonstrate these behaviours for enhanced success of organizational strategy implementation. Enhanced success of effective strategy implementation could improve the overall effective function of the organizations. Contributions, limitations, and implications of the study were also discussed.